Effects on learning of multimedia animation combined with multidimensional concept maps. (January 2015) - Chiou, Chei-Chang; Tien, Li-Chu; Lee, Li-Tze
Abstract: This study investigates whether teaching materials combining multimedia animation and multidimensional concept maps (MAMCMs) improve learning achievement, retention, and satisfaction more than multidimensional concept maps (MCMs), as suggested by Huang et al. (2012) in Computers & Education . Learning retention, learning achievement, and learning satisfaction associated with two sets of course materials were compared in this quasi-experimental study. In total, 114 students from two classes at one private university in Taiwan participated in this 6-week teaching experiment. Analytical results indicate that learning achievement, learning satisfaction, and learning retention of the MAMCM group were better than those of the MCM group. Pedagogical implications and suggestions are given. Highlights: Examining the benefits of multimedia animation with multidimensional concept maps. Multimedia animation with multidimensional concept maps improves learning achievement. Multimedia animation with multidimensional concept maps enhances learning satisfaction. Multimedia animation with multidimensional concept maps improves memory retention.